2012
DOI: 10.1371/journal.pone.0035072
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Inhibits Helicobacter pylori Growth In Vitro and Mice Gastric Mucosa Colonization

Abstract: H. pylori drug-resistant strains and non-compliance to therapy are the major causes of H. pylori eradication failure. For some bacterial species it has been demonstrated that fatty acids have a growth inhibitory effect. Our main aim was to assess the ability of docosahexaenoic acid (DHA) to inhibit H. pylori growth both in vitro and in a mouse model. The effectiveness of standard therapy (ST) in combination with DHA on H. pylori eradication and recurrence prevention success was also investigated. The effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 28 publications
13
86
0
Order By: Relevance
“…The inhibitory effect of polyunsaturated fatty acids on the growth of H. pylori, particularly docosahexaenoic acid and linolenic acids, was reported previously by Thompson et al (1994), Correia et al (2012Correia et al ( , 2013Correia et al ( , 2014 and Obonyo et al (2012). Docosahexaenoic acid pre-treated H. pylori cultures showed a reduction in IL-8 production, and a decrease of cyclooxygenase-2 and inducible nitric oxide synthase by adhesion to gastric epithelial cells.…”
Section: Discussionsupporting
confidence: 71%
“…The inhibitory effect of polyunsaturated fatty acids on the growth of H. pylori, particularly docosahexaenoic acid and linolenic acids, was reported previously by Thompson et al (1994), Correia et al (2012Correia et al ( , 2013Correia et al ( , 2014 and Obonyo et al (2012). Docosahexaenoic acid pre-treated H. pylori cultures showed a reduction in IL-8 production, and a decrease of cyclooxygenase-2 and inducible nitric oxide synthase by adhesion to gastric epithelial cells.…”
Section: Discussionsupporting
confidence: 71%
“…Several studies revealed that consumption of ω-3 PUFAs anti-inflammatory effects while consumption of ω-6 PUFAs produced strong inflammatory factors by locating in cell membrane and metabolization [35]. Correia et al have proved that inhibitory ability of ω-3 PUFAs in bacteria growth and its colonization solely depends on DHA in mice gastric [36,37]. It has been shown that 100 μM concentration of DHA reduces H. pylori growth while concentration greater than 250 μM inhibits the survival of H. pylori irreversibly.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to initiate morphological changes in H. pylori has also been demonstrated for other fatty acids. Correia et al (46) investigated the influence of polyunsaturated docosahexaenoic acid (DHA) on the growth of H. pylori by observing bacterial viability using CFU/mL measurement and by analyzing the morphology of this pathogen. The exposure of H. pylori 26695 and SS1 to 100 μM DHA resulted in the conversion from the spiral to the coccoid form and the initiation of the VBNC state.…”
Section: Communication Of Microorganisms Via Diffusible Signal Factorsmentioning
confidence: 99%
“…After bacterial proliferation in the gastric mucosa, microorganisms enter the stationary phase accompanied by a decrease in AI-2 concentration and an increase in DSFs autoinductive activity. This stage is promoted by another conversion of bacteria to the coccoid form (10,17,31,34,46). The spherical forms display enhanced survival capabilities as shown by the increased potential for autoaggregation, biofilm formation, and biocide resistance.…”
Section: The Holistic Model Of H Pylori Infectionmentioning
confidence: 99%
See 1 more Smart Citation